PEMBANGKITAN TEGANGAN MENGGUNAKAN KARBON AKTIF TEMPURUNG KELAPA DENGAN VARIASI PROSENTASE NACL - Gunawan Tista, Si Putu Gede (POROS, 2023)
Fossil fuels as energy generators have been identified as the main cause of environmental pollution, besides that their supplies are running low. Energy from fossil fuels can cause global warming and climate change due to the carbon dioxide gas emissions produced, causing a greenhouse effect. Therefore, to generate electrical energy, environmentally friendly materials are needed, one of which is coconut shell-activated carbon. This research aims to generate voltage using coconut shell-activated carbon with varying percentages of NaCl. The voltage generation model is composed of counter electrodes – electrodes – counter electrodes. The electrode used is coconut shell-activated carbon, while the counter electrode is copper. The electrolyte used was a NaCl solution with NaCl percentages of 5%, 10% and 15% respectively. The NaCl electrolyte is injected into the model between the electrode and the counter electrode, then heat is applied. An electrostatic force occurs between the ions from the NaCl electrolyte and the surface of the coconut shell-activated carbon, namely the functional groups, pores, and copper counter electrode. The results show that the higher the percentage of NaCl electrolyte, the higher the voltage produced. The resulting voltage is 0.091 volts at a NaCl percentage of 5%, 0.181 volts at a NaCl percentage of 10%, and 0.212 volts at a NaCl percentage of 15%.